Modern genocide : a documentary and reference guide - Bartrop, Paul R. (Paul Robert), 1955- (Documentary and reference guides., 2019)
"This book provides an indispensable resource for anyone researching the scourge of mass murder in the 20th and 21st centuries, effectively using primary source documents to help them understand all aspects of genocide"--